Unusual presentation of acute pancreatitis following high tibial osteotomy. Issue 2 (13th February 2019) - O'Connor, Adam; Asaad, Peter
Abstract : We report a case of a 55-year-old man taxi driver admitted electively for high tibial osteotomy for relief of bilateral medial compartment osteoarthritis. He was obese and an ex-smoker but medical history was otherwise unremarkable. Day 1 postoperatively the patient started to suffer vomiting episodes and the abdomen was distended. C Reactive protein and white cell count were both elevated but other bloods were normal. CT abdomen and pelvis was performed which showed acute interstitial pancreatitis. Glasgow score was calculated as 2. He was treated aggressively with analgesia, intravenous fluid and intravenous antibiotics. He has made a good recovery following these conservative measures. To our knowledge, this is the first case in the literature reporting pancreatitis as a complication of high tibial osteotomy. This case highlights the importance of close monitoring for abdominal complications even in the setting of elective orthopaedic surgery where it is a rare phenomenon.